2017
DOI: 10.3390/s17040861
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Dopamine Using 3D Porous Graphene Oxide/Gold Nanoparticle Composites

Abstract: The detection of dopamine in a highly sensitive and selective manner is crucial for the early diagnosis of a number of neurological diseases/disorders. Here, a report on a new platform for the electrochemical detection of dopamine with a considerable accuracy that comprises a 3D porous graphene oxide (pGO)/gold nanoparticle (GNP)/pGO composite-modified indium tin oxide (ITO) is presented. The pGO was first synthesized and purified by ultrasonication and centrifugation, and it was then further functionalized on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…To avoid this problem, alternatives have been proposed for electrode systems, to obtain greater selectivity and sensitivity. Among them, those that show satisfactory performance to detect biomolecules are those that combine graphene with nanoparticles of metal or metal oxide . In particular, electrochemical biosensors based on electrodes modified with Ag NPs showed high selectivity and sensitivity .…”
Section: Introductionsupporting
confidence: 78%
“…To avoid this problem, alternatives have been proposed for electrode systems, to obtain greater selectivity and sensitivity. Among them, those that show satisfactory performance to detect biomolecules are those that combine graphene with nanoparticles of metal or metal oxide . In particular, electrochemical biosensors based on electrodes modified with Ag NPs showed high selectivity and sensitivity .…”
Section: Introductionsupporting
confidence: 78%
“…The novel CS/N, GQDs @SPCE sensor was employed to detect DA in human urine [111]. Choo et al (2017) developed a 3D porous graphene oxide (pGO) with Au NP composites for DA measurement [112]. An ultrasonic probe was used to prepare pGO then Au NP was incorporated and 3D pGO-Au NP-pGO-modified indium tin oxide (ITO) electrodes were reported as a novel platform to detect DA electrochemically.…”
Section: Carbon-based Ec Sensormentioning
confidence: 99%
“…Electrochemical detection is a simple and convenient technique and has therefore attracted increasing interest for measurement of various neurotransmitters including dopamine, gamma-aminobutyric acid, and serotonin 20 24 . Unlike other biological molecules such as glucose, dopamine is highly redox active and can effectively be measured without the use of other redox couples and/or enzymes required to facilitate the reduction/oxidation of the target molecules 19 , 25 30 . However, one critical concern for the detection of dopamine in blood is its low concentration level 1 , 5 , which is further amplified by the signal interference from other biological molecules such as glucose, ascorbic acid (AA), and uric acid (UA).…”
Section: Introductionmentioning
confidence: 99%
“…However, one critical concern for the detection of dopamine in blood is its low concentration level 1 , 5 , which is further amplified by the signal interference from other biological molecules such as glucose, ascorbic acid (AA), and uric acid (UA). To this end, numerous studies have reported a variety of platforms by mostly integrating conductive micro-/nanomaterials or polymers on the surface of electrodes 30 . Owing to the high conductivity and excellent electrocatalytic properties, metals such as gold, silver, and platinum have been modified on the electrode surface, mostly in the form of nanoparticles/nanostructures, to take advantage of their high surface-to-volume ratios.…”
Section: Introductionmentioning
confidence: 99%